Transforming learning: incorporate virtual exhibitions into teaching - Zainal Abidin, Hazlin Anita; Maharam, Mohd Erman (Penerbit UiTM (UiTM Press), 2026)
Advancements in digital technologies present exciting opportunities for art curators and educators to develop engaging art exhibition activities. Digitalisation effectively addresses challenges such as limited resources, funding, and technical support that often confront not only arts professionals but also, more critically, educators in higher education. These challenges are particularly significant for archiving, curating, and exhibiting projects centred on popular culture, especially those related to the entertainment industry. This paper posits that art educators can leverage digital technologies to train future curators and art exhibition specialists by incorporating virtual exhibitions into their syllabi and practices. This approach unlocks new opportunities for exploration within the field and enhance students understanding of exhibitions and curatorship through digital technologies. This paper aims to share our experiences from a semester-long exhibition and curatorship course offered as part of the Arts Management program at Universiti Teknologi MARA, Puncak Perdana Campus. The project, titled ‘Let’s Digital,’ is founded on three key pillars: robust support for technology in the archiving of digital data, curating, and exhibiting; the flexibility to cultivate new concepts and technologies in diverse environments; and the fostering of technological proficiency to equip students with essential lifelong learning skills for future workforce success. This technology-integrated, creative educational approach to preserving and curating exhibitions aims to provide students with flexible learning opportunities. Through these processes and by embedding technology, they acquire knowledge of Malaysian popular culture, developing theoretical and practical digital skills that enhance their personal development and deepen their understanding of exhibitions and curatorial practices in the digital age.